Níveis crescentes de óleo de soja em dieta baseada em capim-elefante (Pennisetum purpureum Schumack) picado sobre parâmetros da fermentação e cinética ruminal, composição e perfil de ácidos graxos do leite de vacas mestiças - Carlos Gustavo Santos Ribeiro (2009)
This dissertation was composed of two distinct experiments, the objective of the first experiment was to evaluate the influence of the addition of four different levels of soybean oil (SO) (0, 1.5, 3.0 and 4.5% of dry matter, DM) in diets based on chopped elephant grass on the lipid composition of milk of twelve crossbred Holstein x Zebu cows with average production equal to 18.0 ± 4.6 kg/day of milk and mean body weight of 502.6 ± 47.8 kg. The cows were distributed in three 4x4 Latin Squares (LS). Each phase of the LS extended by 15 days, the first ten days for diet adaptation and the last five for collection of data and samples. We analyzed the fatty acids (FA) profiles of the food (elephant grass, concentrate and soybean oil) and the butter milk. The data presented showed that the concentrate FA composition was stable even seven days of air exposure. About the butter, the concentrations of short (C4 to C10), medium (C12 to C16) and saturated chain FA were reduced (P<0.01). In contrast, the oil increased the concentration of C18:1 trans-11 (P<0.01) and C18:1 trans-10 (P<0.01) FA. There was an increase (P<0.01) on the concentration of all 18C FA, saturated and monounsaturated. The oleic acid C18:1 cis-9 was the cis isomer and vaccenic acid C18:1 trans-11 the trans isomer with highest concentrations. Except for the isomers C18:3 iso1 and C18:3 iso2, the levels of branched-chain odd FA reduced (P<0.01) expressively. The nutraceutical characteristics of the butter were satisfactory, there was some increase (P<0.01) in the mono, polyunsaturated and total unsaturated FA (44, 54 and 43% between treatments with the addition of 0 and 4.5% of SO, respectively). There was also a decrease (P<0.01) in the proportion of saturated FA by 25% (for diets with 0 and 4.5% of SO). The concentration of all CLA isomers increased linearly (P<0.01). Between the treatments 0 and 4.5% of SO, the total concentration of CLA increased about 361.5% (from 1.31 to 4.70 g/100 g). The C18:2 cis-9 trans-11 isomer accounted for approximately 98% of total CLA and increased 358.6% (from 1.28 to 4.59 g/100 g). There was a high correlation (r2=0.942) between the vaccenic acid and C18:2 cis-9 trans-11 CLA (y = 0.448 x + 0.546), between the reduction of the milk fat content and the increasing concentration of C18:2 trans-10 cis-12 CLA (y = -16.44 x +3.3, r2=0.296) and the C18: 2 cis-9 trans-11 CLA (y = -10.41 x +3.49, r2=0.397). The content and daily production of fat decreased linearly (P<0.01 and P=0.03, respectively). It probably reflects the considerable secretion of isomers of CLA C18:2 trans-10, cis-12 and C18:2 trans-9, cis-11, known inhibitors of secretion of fat in mammary gland. The lactose content decreased (P=0.02) 0.15%, between control and 4.5% of SO. Unlike the literature, the content of milk protein increased (P<0.03) their values. The same behavior was not observed in the daily production of protein. As new information, we observed that there is difference (P<0.05) between the FA profile in the milk milked in the morning and afternoon. The second experiment of this dissertation was made to evaluate the consumption of dry matter, the rumen parameters and gastrointestinal kinetic of cows fed diets based on chopped elephant grass supplemented with increasing levels of SO (0, 1.5, 3.0 and 4.5%) in a 4x4 Latin Square. We used four rumen fistulated crossbred Holstein x Zebu cows, in the initial fase of lactation (90 ± 25 days) and average production of 15.6 ± 3.0 kg of milk/day. The daily DM intake was not affected (P>0.05) for the soybean oil added at levels equal to or lower than 4.5% of the diet (13.4, 13.8, 14.5 and 13.7 kg/day or 2.90, 3.02, 3.17 and 2.93% BW/day for treatments with 0, 1.5, 3.0 and 4.5% for SO, respectively). Among the rumen fermentation parameters, only the concentration of ruminal propionate and butyrate and the molar concentration of butyrate were influenced (P<0.05) by treatments. Was observed small influence of different treatments on DM consumption and ruminal parameters, it seems that the addition of soybean oil up to 4.5% of the DM showed little influence at the microbial population of the rumen. This assumption confronted with the results observed in in situ digestibility. Among the parameters of in situ ruminal degradability of DM and OM, both the rate of degradation (c) (4.00, 3.32, 3.26 and 2.71%/h and 4.1 for MS, 3 , 5, 3.3 and 3.0%/h for the MO for the treatments with 0, 1.5, 3.0 and 4.5% for OS, respectively) and effective degradability (ED) (35.09 , 32.64, 33.54 and 31.04% for DM and 42.26, 39.98, 40.31 and 39.13% for the OM for the treatments with 0, 1.5, 3.0 and 4.5% for OS, respectively) reduced their values (P<0.07 and P<0.10, respectively) with the addition of SO. Among the parameters of NDF in situ ruminal degradability, only ED was affected (P<0.07) (23.19, 21.04, 22.21 and 19.46% for treatments with 0, 1.5, 3.0 and 4.5% for SO, respectively). None of the kinetic parameters of the liquid or solid phase flow was affected (P<0.05) of adding soybean oil. There was no interaction between treatments and time of sampling in any of the observed parameters.